Cities through the looking glass essays on the history and archaeology of Biblical urbanism - Arav, Rami 1947- (Winona Lake, Ind. Eisenbrauns, 2008)
The essays in this book originated as papers presented at the Conference on Urbanism in the Biblical World that took place on October 28-30, 2003, at the University of Nebraska at Omaha. This conference was part of the annual series of the Clifton Batchelder Conference for Biblical Archaeology and the Bethsaida Excavations Project. The conference was structured so that text scholars and material-culture scholars were able to interact and influence one another. This interdisciplinary approach created a unique, productive atmosphere where scholars who come from different disciplines were able to share and exchange ideas in ways that seldom happen in our increasingly specialized academic world. Thus, scholars from three major disciplines - Greek philosophy, biblical studies, and archaeology - produced lectures and papers on urbanism in the ancient world that reflect multihued perspectives that draw on the specialties of each contributor.Few conferences on urbanism engage in an interdisciplinary approach, and few deal with the questions raised in this book; even fewer are published and see the light of day. In this volume, we are pleased to be able to share a fine collection of essays from the conference with the larger community of people interested in the ancient world.
"... inspired by papers presented at the Conference on Urbanism in the Biblical World ... October 28-30, 2003, at the University of Nebraska at Omaha"
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Antiquities; Cities and towns, Ancient -- Middle East; Urbanization -- Middle East; Cities and towns -- Biblical teaching; Middle East -- Antiquities; Konferenzschrift -- 2003 -- Omaha, Neb; Konferenzschrift